The Ethics of AI in Medical Research: A Call for Open and Honest Discussion - Shazma Tahseen; Memon, Muhammad Ali; Kamran, Shah Muhammad; Pathan, Kamran Taj (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Artificial intelligence (AI) in healthcare is gaining rapid popularity in terms of its application and research. A significant reason for its success is due to the advances it has made and the ease of use it incorporates. Because of its implications, issues, and benefits in terms of ease, AI has been debated and researched extensively. This study examined the ethical dilemmas associated with artificial intelligence in medical research. The research uses a qualitative research method based on content analysis. Authentic Internet resources were used to collect secondary data. Once AI is fully integrated into healthcare, several ethical dilemmas will likely arise, including patient privacy, data security, algorithmically biased results, transparency, and human error. Minimizing ethical dilemmas with continuous monitoring is possible, but they cannot be eliminated. It is possible with the advancement of technology and AI enables it to imitate the cognitive processes of humans, which may enhance its reliability but can also lead to negative consequences. As a result, the new technological developments must be applied ethically. An open and honest discussion is essential for the awareness and understanding of AI ethics, honoring patient rights, and maintaining public trust.